Geofï¿½sica aplicada no controle estrutural na ï¿½rea do domo de Piratininga (SP) - Braga, Antonio Celso de Oliveira [UNESP]; Dourado, Joï¿½o Carlos [UNESP]; Birelli, Carlos Alberto; Blanco, Rï¿½gis Gonï¿½alves; Francisco, Richard Fonseca [UNESP] (My University, 2016)
This paper presents the results obtained from geophysical data processing, wich were acquired through vertical electrical soundings developed in the Dome of Piratininga/SP region. These geoelectric data were carried out by the Institute for Technological Research (IPT) in the 1970s and 1980s, taking into account the consortium Paulipetro request. Generally, the purpose of this project was to characterize the stratigraphy of the Paraná Sedimentary Basin in São Paulo state, providing support to studies focused on the promising aquifers prospection and structures favorable to the occurrence of oil and natural gas. Based on these data, this study aimed to delineate the structural outlines of the Serra Geral and Botucatu formations, including the Crystalline Basement in the Piratininga Dome region. The geophysical surveys coupled to wells data produced satisfactory results, in terms of characterization of the regional geology and delineation of structures outline, highlighting the structural high concerning to the Piratininga Dome. In addition, the results showed a region without occurrence of basalts, located in the Dome area, whose sandstones of Bauru Group probably are in contact directly with the sandstones of Botucatu Formation.
Geophysics applied to structural control in the Piratininga Dome area (SP)